2019
DOI: 10.1002/jbmr.3745
|View full text |Cite
|
Sign up to set email alerts
|

Combined Collagen-Induced Arthritis and Organic Dust-Induced Airway Inflammation to Model Inflammatory Lung Disease in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by extra‐articular involvement including lung disease, yet the mechanisms linking the two conditions are poorly understood. The collagen‐induced arthritis (CIA) model was combined with the organic dust extract (ODE) airway inflammatory model to assess bone/joint–lung inflammatory outcomes. DBA/1J mice were intranasally treated with saline or ODE daily for 5 weeks. CIA was induced on days 1 and 21. Treatment groups included sham (saline injection/saline inhalation), CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…We did not consider these exposure in our findings. A recent animal study has, however, shown that inhalation to organic dust exposure from swine confinement feeding facilities led to airway inflammation and arthritis among male mice 24…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider these exposure in our findings. A recent animal study has, however, shown that inhalation to organic dust exposure from swine confinement feeding facilities led to airway inflammation and arthritis among male mice 24…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the combination of the collagen-induced arthritis (CIA) model with a model of airborne biohazard exposure (e.g. agriculture related-organic dust extract/ODE) resulted in augmented arthritis inflammatory score and bone deterioration, increased systemic autoimmunity with increased anti-cyclic citrullinated peptide IgG antibodies, and promotion of prefibrotic inflammatory lung changes in mice [11] consistent with RA-associated lung disease pathophysiology. However, the mechanisms underlying these observations are not known.…”
Section: Introductionmentioning
confidence: 88%
“…However, insight into how inhalant injury might lead to or exacerbate RA and its pulmonary manifestations, has been limited in the absence of a relevant disease model. Recently a pre-clinical animal model to provide insight into the important cellular players and decipher molecular and potential mechanistic pathways involved in RA-associated inflammatory lung disease was established [11]. Specifically, the combination of the collagen-induced arthritis (CIA) model with a model of airborne biohazard exposure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On Day 1, DBA/1J strain mice were given a subcutaneous injection of 2 mg/ml of chick CII emulsified in FCA 38 . At Week 3, the mice were given the booster injection of chick CII emulsified in FIA.…”
Section: Animal Models Of Ra‐ildmentioning
confidence: 99%